A165 SHORT INJECTION CESSATION EPISODES AS OPPORTUNITIES FOR HEPATITIS C PREVENTION. (1st March 2018) - Fortier, E; Artenie, A; Jutras-Aswad, D; Roy, É; Grebely, J; Bruneau, J
Abstract: Background: In Canada, the majority of new and existing cases of hepatitis C virus (HCV) infection occur among people who inject drugs (PWID), mostly through receptive sharing of injection material. Injecting drug use has been shown to be a dynamic process characterized by transitions in and out of injection. We have previously shown that short injection cessations are associated with a reduced risk of receptive sharing of injection material when resuming injection. Aims: This investigation aimed to assess the association between HCV infection and intermittent injecting drug use, when considering one-month injection cessation episodes. Methods: The HEPCO study is an observational cohort of PWID recruited and followed longitudinally in Montréal (QC). At 3-month intervals, uninfected participants (HCV RNA-negative) enrolled between March 2011 and December 2014 were tested for HCV, and completed an interviewer-administered questionnaire eliciting information on sociodemographics, drug use, and related behaviors and treatments. Participants were at-risk of either primary HCV infection (anti-HCV-negative participants), or reinfection/recurrence (anti-HCV-positive participants). Injecting drug use in the past 3 months was categorized as follows: injecting within 0 (no use), 1 or 2 (intermittent use), or 3 months (continuous use). HCV infection was estimated to occur at the midpoint between two visits. Cox regression analyses with time-dependent covariates were performed, and Kaplan–Meier failure curves for multiple-record-per-subject data were estimated. Results: 311 participants with ≥1 follow-up visit (mean age 40 years, 82% male, 47% anti-HCV positive) contributed 1, 689 visits. HCV incidence was 11.3 per 100 person-years [95% confidence interval (CI), 8.8–14.4]. At baseline, 188 (60%), 79 (25%) and 44 (14%) participants reported continuous, intermittent and no injecting drug use in the past 3 months, respectively. In univariate Cox models, intermittent and no injecting drug use were significantly associated with a reduced risk of HCV infection [intermittent use: hazard ratio (HR) 0.36, 95%CI 0.17–0.77; no use: HR 0.23, 95%CI 0.09–0.58] compared to continuous use. In models adjusted for age, gender and opioid substitution treatment, associations remained statistically significant for both intermittent (HR 0.40, 95%CI 0.19–0.86) and no injecting drug use (HR 0.30, 95%CI 0.12–0.77). There was no evidence of effect modification by anti-HCV status at baseline. Conclusions: Intermittent injecting drug use was associated with a reduced risk of HCV infection. Findings bring new perspectives regarding injecting profiles and their relation to HCV risk, and for improving PWID's access to clinical care and harm reduction interventions. Further work is needed to contextualize intermittent injecting drug use in the injecting drug use trajectory. Funding Agencies: CIHRFRQS